At the roots of contemporary modernity: declinations of sovereignty and metamorphosis of the subject in 20th century Europe (Italian Review of Legal History, 2023)
The contribution aims to investigate the relationship between civil and political society between the nineteenth and twentieth centuries, up to the birth of the Italian Republic and to verify how much the rift in it influenced the stability of the constitutional order, producing its transformation. The investigation is carried out considering the importance of the relationship between the constitutional model and the anthropological paradigm under it and also capturing its reflections on the different forms that sovereignty progressively takes on over the period considered. The starting point is identified in the reversion of the position between law and politics brought by the French Revolution, with the systematic subjection of the former to the latter. The point of arrival is identified in the reconciliation between the first and the second, carried out during the work of the Constituent Assembly in the years between 1946 and 1947. The anthropological paradigms that follow one another over time are the individualist one, the organicist one and the personalist one, the latter of which represents the basis on which the 1948 Constitution was built.
Keywords: Individualism; Organicism; Personalism; Sovereignty; Representation; Civil society; Political society